Detection of Extended spectrum β -lactamases (ESBLs) produced by Acinetobacter baumannii isolated from burn patients in Al- Nasiriyah city Iraq. - Safaa Majid Kadom Flayyih; Intidhaar Naeem Abid (University of Thi-Qar Journal of Science, 2022)
The aim of present study is to isolate and identify of Acinetobacter baumannii from burns  infect as well as study their  production for Extended spectrum β -lactamases (ESBLs).This study included 205 burn patients at Al-Hussien Teaching Hospital and other burn care units in Al-Nasiriyah city . The specimens were collected during period from August  2018 to February 2019. It were taken by burn swabs from pus of the burned area and then inoculated on blood agar and MacConkey agar. The isolates were diagnosed by microscopic examination, biochemical tests , API 20 E and Vitek- 2 system . It was found that 20 isolates of A.baumannii and 2  isolates of A. loffii . Where identified from this study . The study showed 18 (90%) out of 20 isolates of A. baumannii  were appeared resistance to cefotaxime and  ceftazidime(screening test of ESBLs) . Seven (35%) of isolates were producing ESBLs  by confirmatory test(Modified double –disk synergy test (MDDST)) , and 13(65%) of isolates were negative results to production of the ESBLs.